The impact of social capital and mental health on medication adherence among older people living with HIV (PLWH) - Lei He; Bin Yu; Jun Yu; Jun Xiong; Yuling Huang; Tian Xie; Qi Chai; Bo Gao; Shujuan Yang (BMC, 2021)
Abstract Background The number of older people living with HIV (PLWH) is increasing. Although there are many studies affecting medication adherence, research on the impact of social capital and mental health on medication adherence in this particular population is limited. Method Data were collected from an ongoing observational prospective cohort study, starting from November 2018, among older PLWH in Sichuan province, China. Five hundred twenty-one participants were interviewed. Social capital consists of the individual and family (IF) scale, and the community and society (CS) scale. The presence of probable depression and probable anxiety were assessed using the CES-D-10 and GAD-7 scales. Adherence was defined as taking ≥80% of prescribed HIV medication in 4 days prior to the interview. Two sets of Firth' penalized regression analyses were used to estimate the association between social capital, mental health, and medication adherence. Results The prevalence of non-adherence was 18.2% (95/521) among older PLWH in this study. After adjusting for significant factors, the CS social capital (OR: 0.92, 95%CI:0.85-0.99, p < 0.05) and probable anxiety (OR:1.73, 95%CI:1.07-2.80, p < 0.05) were associated with non-adherence. Conclusion This study highlighted that the effects of social capital and mental health on older PLWH's adherence, which implied that the need to develop interventions to concern for mental health and enhance CS social capital to help the older PLWH better manage HIV medication adherence.